Scrum For Dummies - and Layton, Mark C. (John Wiley & Sons, 2015)
Practice an agile form of management to stop wasting time and money Scrum For Dummies is an easy to use guide to managing the tricky transition from a traditional project management methodology to the new and most popular agile framework. As the most efficient, successful methodology for team project management, Scrum relies on transparency, flexibility, and fluidity to deliver a final product that fulfills the needs of all stakeholders. Written in easy–to–read Dummies style, this book walks you through the core principles of Scrum and provides a roadmap for tangible implementation. The vast majority of projects go over budget, and billions of dollars are wasted every year on overruns. Put a stop to this wasteful leakage by switching to a management style that keeps all participants informed, up–to–date, and accountable. Authored by a Certified Scrum Trainer, Mark Layton, Scrum For Dummies covers the key ideas and processes behind Scrum methodologies, and presents the inner workings of the plan in an engaging and accessible format. Topics include: The Scrum values, roles, artifacts, and activities that make up the principle of this methodology When and how best to use Scrum The differences between Scrum and other agile methodologies Using Scrum for IT, finance, construction, health care, and more The book also delves into the everyday use of Scrum, and how it can help you achieve your own personal goals outside of work. There's a reason why scrum is quickly becoming the standard approach to project management it works! If you want to stop wasting time and start producing more effectively, Scrum For Dummies is the guide that will get you there.